Pro-poor tax reforms, with an application to Mexico - Jean-Yves Duclos; Paul Makdissi; Abdelkrim Araar (Institute for the Study of Labor (IZA), 2009)
This paper proposes a methodology for testing for whether tax reforms are pro-poor. This is done by extending stochastic dominance techniques to help identify tax reforms that will necessarily be deemed absolutely or relatively pro-poor by a wide spectrum of poverty analysts. The statistical properties of the various estimators are also derived in order to make the method implementable using survey data. The methodology is used to assess the pro-poorness of possible reforms to Mexico's indirect tax system. This leads to the identification of several possible pro-poor tax reforms in that country. It also shows how the pro-poorness of a tax reform depends on one's conception of poverty as well as on the revenue and efficiency impact of the reform.
urn:nbn:de:101:1-20091105826
Keywords: D12; D63; H21; I32; 330; Stochastic dominance; pro-poor changes; tax reforms; Mexico; Armutspolitik; Steuerreform; Mexiko